2008
DOI: 10.1016/j.drugalcdep.2007.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Non-prescribed use of pain relievers among adolescents in the United States

Abstract: Background-We examined gender-specific prevalences, patterns, and correlates of nonprescribed use of pain relievers-mainly opioids-in a representative sample of American adolescents (N = 18,678).Methods-Data were drawn from the public use data file of the 2005 U.S. National Survey on Drug Use and Health, a survey of non-institutionalized American household residents. The patterns of nonprescribed use of prescription pain relievers were examined, and logistic regression procedures were conducted to identify cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
133
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 29 publications
11
133
4
1
Order By: Relevance
“…Cross-sectional national data have shown that the average age of onset for NMU of pain relievers was approximately the same as for alcohol (e.g., 13 years) [17]. However, a recent longitudinal study conducted by Catalano et al found that prevalence of NMU of pain relievers peaks at age 17 years [8].…”
Section: Am Young Et Al / Journal Of Adolescent Health 51 (2012) 6mentioning
confidence: 97%
See 4 more Smart Citations
“…Cross-sectional national data have shown that the average age of onset for NMU of pain relievers was approximately the same as for alcohol (e.g., 13 years) [17]. However, a recent longitudinal study conducted by Catalano et al found that prevalence of NMU of pain relievers peaks at age 17 years [8].…”
Section: Am Young Et Al / Journal Of Adolescent Health 51 (2012) 6mentioning
confidence: 97%
“…Studies have identified several other correlates of adolescent NMUPM, including residential instability [16,20], rurality [10,13,17], poor self-reported health [8,10,17], recent major depressive episode [10,16], posttraumatic stress disorder [18], mood disorder [8], mental health service utilization [16,17,21], and emergency room use [17]. NMUPM, particularly that of sedatives and pain relievers, has also been associated with sexual victimization [33,34].…”
Section: Am Young Et Al / Journal Of Adolescent Health 51 (2012) 6mentioning
confidence: 98%
See 3 more Smart Citations